Evaluation of nutritional status among children aged 7-10 - Paulina Sztandera; Beata Szczepanowska-Wołowiec; Ireneusz Kotela (Journal of Education, Health and Sport, 2017)
Introduction and aim of the study. The prevalence of overweight and obesity among the children and adolescents is particularly dangerous, in 60% of children and adolescents, this problem will occur in adulthood, and also increases the risk of diseases such as: type 2 diabetes, hiprelipidemia, hypertension, or emotional disturbances. The aim of the study was evaluation of nutritional status among children aged 7-10 years old from Masłów and Górno District measured by BMI index.